Konseling Individu Teknik Behavior Contract untuk Mengurangi Perilaku Membolos Sekolah di SMK - Titis Indari (Universitas Negeri Malang, 2023)
Abstract: Truancy behavior that are common are maladaptive behaviors that are often experienced by students at school. Behavior occurs due to the inability of students to adapt to environmental demands. The behavior contract technique which aims to change individual behavior can be a solution to this maladaptive action. This technique is done with good awareness and commitment between the counselor and the client. The basic principles in the behavior contract technique include: (1) contracts are carried out with reinforcement, (2) strengthening must be carried out immediately, (3) contracts are negotiated freely and openly and are mutually agreed upon, (4) contracts are fair and clear, (5) contracts have clear target behavior behavior, frequency and duration of contracts, (6) contracts integrated with school programs. The use of individual counseling services with the behavior contract technique can be applied by counselors so that clients have awareness and eliminate truancy in high school. Abstrak: Membolos merupakan perilaku maladaptif yang sering dialami siswa di sekolah. Perilaku terjadi akibat ketidakmampuan siswa dalam menyesuaikan diri dengan tuntutan lingkungan. Teknik behaviour contract yang bertujuan mengubah perilaku individu dapat menjadi solusi atas tindakan maladaptif tersebut. Teknik ini dilakukan dengan kesadaran dan komitmen yang baik antara konselor dengan konseli. Prinsip dasar dalam teknik behaviour contract, antara lain: (1) kontrak dilakukan dengan penguatan, (2) penguatan harus segera dilakukan, (3) kontrak dinegosiasi secara bebas dan terbuka serta disepakati bersama, (4) kontrak adil dan jelas, (5) kontrak memiliki kejelasan target tingkah laku, frekuensi dan lamanya kontrak, (6) kontrak terintergritas dengan program sekolah. Penggunaan layanan konseling individu dengan teknik behavior contract dapat terapkan konselor sehingga konseli mempunyai mempunyai kesadaran dan menghapus perilaku membolos di sekolah.